BJSS 2021
DOI: 10.21776/ub.bjss.2021.001.01.1
|View full text |Cite
|
Sign up to set email alerts
|

Kerentanan Sosial Ekonomi dan Resiliensi Keluarga Petani Miskin Selama Pandemi COVID-19: Kasus Dari Madura

Abstract: The Covid-19 pandemic, in addition its health impacts, also has a serious impact to people's socioeconomic vulnerabilities. Socio-economic vulnerabilities due to the Covid-19 pandemic forced people to adapt, one of which was a poor peasant family in rural Madura. This article presents the results of research focusing on the socio-economic vulnerability of poor peasant family as well as various efforts in dealing with the Covid-19 pandemic. Using descriptive qualitative approach and data collection method throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…The adaptations that have been made are reducing the workforce to become family workers, reducing grain sales, and doing various side jobs. This is also the case with the research results of Zaeni et al (2022) which showed that the survival strategy adopted by cut flower farming households during the COVID-19 pandemic in order to be able to meet their household needs was by doing side jobs, increasing hours or work intensity, implementing patterns double income, selling assets owned, reducing (Sabariman & Susanti, 2021) explain the same thing. Adaptation strategies carried out by poor farming families in rural areas, namely: building group solidarity according to developing values and norms, utilizing very strong family ties, and minimizing household expenses and utilizing social networks for business development.…”
Section: Passive Strategymentioning
confidence: 67%
“…The adaptations that have been made are reducing the workforce to become family workers, reducing grain sales, and doing various side jobs. This is also the case with the research results of Zaeni et al (2022) which showed that the survival strategy adopted by cut flower farming households during the COVID-19 pandemic in order to be able to meet their household needs was by doing side jobs, increasing hours or work intensity, implementing patterns double income, selling assets owned, reducing (Sabariman & Susanti, 2021) explain the same thing. Adaptation strategies carried out by poor farming families in rural areas, namely: building group solidarity according to developing values and norms, utilizing very strong family ties, and minimizing household expenses and utilizing social networks for business development.…”
Section: Passive Strategymentioning
confidence: 67%
“…Also, immediately repair sugarcane plants when damaged, which can be caused by strong winds or pests (Azmi et al, 2023). The adaptation strategy is carried out by poor farming families in rural Madura to deal with stress from the COVID-19 pandemic, namely by building group solidarity according to developing values and norms: cooperation, helping each other in the form of sharing food or basic needs, reciprocity labor services/work bartering, usually of a personal nature and in a productive and helpful field (Sabariman, H. 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini dikarenakan sektor pertanian merupakan sektor yang dapat bertahan dan tetap dapat dijalankan selama pandemi Covid-19, karena pada dasarnya demand hasil bumi akan selalu terus ada sebagai kebutuhan pangan sehari-hari masyarakat meskipun juga terdampak oleh adanya pandemi Covid-19. Temuan dalam penelitian ini selaras dengan hasil penelitian (Sabariman & Susanti, 2021) yang menyatakan bahwa keluarga petani miskin di pedesaan mampu bertahan dan berkembang dalam menghadapi pandemi Covid-19, dimana keluarga petani miskin tidak mengalami dampak yang berkepanjangan karena mereka mempunyai kemampuan pengelolaan dalam masa sulit. Salah satu contohnya adalah dengan masih bertumpu pada adat budaya dalam mengelola lahan pertaniannya.…”
Section: Dampak Strategi Nafkah Terhadap Kehidupan Petani Selama Pand...unclassified